1972
DOI: 10.1111/j.2042-7158.1972.tb08944.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of dextrose degradation under autoclaving conditions

Abstract: The kinetics of the decomposition of dextrose have been investigated over a temperature range of 106" to 127". The reaction is shown to exhibit an induction period with respect to 5-hydroxymethylfurfural production which is due to the formation of an intermediate compound. A reaction mechanism is proposed which appears consistent with the experimental measurements. Rate constants are calculated for the various reaction steps and the activation energies associated with these steps are reported.Dextrose decompos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…Sample degradation procedures. Glucose degradation by heat has been well documented, and is generally accepted to follow pseudo-zero (lo), or first order (8,9) kinetics. T h e major degradation product, 5-HMF, is formed through intermediates, as yet unidentified.…”
Section: Methodsmentioning
confidence: 99%
“…Sample degradation procedures. Glucose degradation by heat has been well documented, and is generally accepted to follow pseudo-zero (lo), or first order (8,9) kinetics. T h e major degradation product, 5-HMF, is formed through intermediates, as yet unidentified.…”
Section: Methodsmentioning
confidence: 99%
“…Both low and higher molecular weight aldehydes are generated from glucose degradation after the heat sterilization procedure during the manufacture of the solutions. [1][2][3][4][5][6] Aldehydes have also been discovered in freezing solutions, caused by the autoxidation of the cryoprotective compounds. 7 In vitro studies have demonstrated that aldehyde toxicity diminished the viability of frozen mouse oocytes and zygotes; as well as fibroblasts and peritoneal mesothelial cells in culture.…”
Section: Introductionmentioning
confidence: 99%
“…Before use, samples were analyzed for the presence of intermediate products of the nonenzymatic degradation of glucose at wavelengths of 228 and 284 nm, using a UV-1202 UV-vis Spectrophotometer (Shimazu, Kyoto, Japan) [14]. Under these conditions, the glucose-enriched, filter-sterilized solution did not show absorption.…”
Section: Methodsmentioning
confidence: 99%